A fertile cooperation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The collaborating authors of whom half are African of this compilation of scientific papers on nutrient management is to develop practices to maintain or improve nutrient balances by using an optimum mix of local organic nutrients and inorganic fert